If x = sec ϕ - tanϕ and y = cosec ϕ + cot ϕ then show that xy + x -y +1=0.

0 votes
1 view
asked Feb 17, 2018 in Class XI Maths by rahul152 (-2,844 points)
If x = sec ϕ - tanϕ and y = cosec ϕ + cot ϕ then show that xy + x -y +1=0.

Please log in or register to answer this question.

2 Answers

0 votes
answered Feb 17, 2018 by nikita74 (-1,022 points)

If x = sec ϕ - tanϕ and y = cosec ϕ + cot ϕ then show that xy + x -y +1=0.

0 votes
answered Jun 5 by lab Basic (36 points)

We need to eliminate  2A=ϕ 

y=cosec2A+cot2A=(1+cos2A)/sin2A=cot A

x=sec2A-tan2A=(1+1/y^2)/(1-y^2)-(2/y)(1-1/y^2)=(y^2+1)(y^2-1)-2y/(y^2-1)=(y-1)/(y+1)

Related questions

0 votes
1 answer